Breast cancer genetic testing awareness, attitudes and intentions of Latinas living along the US-Mexico border: a qualitative study - Chalela, Patricia (J Community Med Health Educ, 2012)
BACKGROUND: Genetic testing for breast cancer may facilitate better-informed decisions regarding cancer prevention, risk reduction, more effective early detection, and better determination of risk for family members. Despite these potential benefits, significant portions of the US population—particularly Latinas—lack awareness of genetic testing for breast cancer susceptibility. Among women who are tested, less than 4% are Latina. To uncover reasons for Latinas’ low participation, this study explores awareness, attitudes and behavioral intentions to undergo genetic testing among average-risk Latinas along the Texas-Mexico border. METHODS: Eight focus groups were conducted with 58 Latinas aged 19–69 living in Hidalgo County, a largely Latino region of South Texas. Focus group discussions were digitally recorded, transcribed and analyzed using qualitative content analysis to assess, categorize and interpret them. Two experienced study team members analyzed transcripts to identify major concepts grouped into theme categories. RESULTS: Participants mostly had less than a high-school education (43%), spoke primarily Spanish (52%), were of Mexican-American origin (90%) and had a family income of $30,000 or less (75%). Focus groups found that most participants had positive attitudes and strong interest in genetic testing, yet lacked general awareness and knowledge about genetic testing, its risks, benefits, and limitations. Participants also identified several key cultural-based influencers, such as family, religious beliefs and fear of testing. CONCLUSION: The delivery of culturally adapted risk information is needed to increase and ensure Latinas’ understanding of breast cancer genetic testing during their decision-making processes. Key Latino values—religiosity, importance of family and the influential role of health care providers in health decisions—should also be considered when designing interventions targeting this specific group. Further research is needed to identify effective ways to communicate genetic risk susceptibility information to Latinas to help them make informed testing decisions.